Hydroboration and reductive amination of ketones and aldehydes with HBpin by a bench stable Pd(ii)-catalyst. Issue 5 (14th January 2022) - Mahato, Shreya; Rawal, Parveen; Devadkar, Ajitrao Kisan; Joshi, Mayank; Roy Choudhury, Angshuman; Biswas, Bhaskar; Gupta, Puneet; Panda, Tarun K.
Abstract : A Pd(ii ) complex catalysed hydroboration and reductive amination reaction of several aldehydes and ketones are reported. DFT-based computational study of the reaction mechanism unravels the dual role of HBpin in accomplishing the hydroboration reaction. Abstract : A palladium(ii ) complex [(κ 4 -{1, 2-C6 H4 (NCH–C6 H4 O)2 }Pd] (1 ) supported by a dianionic salen ligand [1, 2-C6 H4 (NCH–C6 H4 O)2 ] 2− (L ) was synthesised and used as a molecular pre-catalyst in the hydroboration of aldehydes and ketones. The molecular structure of Pd(ii ) complex 1 was established by single-crystal X-ray diffraction analysis. Complex 1 was tested as a competent pre-catalyst in the hydroboration of aldehydes and ketones with pinacolborane (HBpin) to produce corresponding boronate esters in excellent yields at ambient temperature under solvent-free conditions. Further, the complex 1 proved to be a competent catalyst in the reductive amination of aldehydes with HBpin and primary amines under mild and solvent-free conditions to afford a high yield (up to 97%) of corresponding secondary amines. Both protocols provided high conversion, superior selectivity and broad substrate scope, from electron-withdrawing to electron-donating and heterocyclic substitutions. A computational study based on density functional theory (DFT) revealed a reaction mechanism for Pd-catalysed hydroboration of carbonyl species in the presence of HBpin. The protocols also uncovered the dual role of HBpin in achieving the hydroboration reaction.